Multimodal DTI-ALPS and hippocampal microstructural signatures unveil stage-specific pathways in Alzheimer’s disease progression - Yu, Peng; Shen, Lu; Tang, Lijun (Frontiers in Aging Neuroscience, 2025)
ObjectiveDevelop a multimodal biomarker framework integrating DTI-ALPS (Diffusion Tensor Imaging along the Perivascular Space), hippocampal diffusivity, and CSF profiles for staging Alzheimer’s disease (AD) progression across the HC → MCI → AD continuum.MethodsCross-sectional analysis of 60 age-matched participants [18 healthy controls (HC), 20 with mild cognitive impairment (MCI), and 22 with Alzheimer’s disease (AD)] combining 3 T MRI-derived biomarkers (bilateral hippocampal fractional anisotropy (FA) and mean diffusivity (MD), and DTI-ALPS). Cerebrospinal fluid (CSF) analysis (Aβ42, p-tau181, t-tau), and cognitive assessments (MMSE, MoCA). Statistical analyses included ANOVA with Bonferroni correction, Pearson correlations, and ROC curve evaluation for disease classification.ResultsDTI-ALPS exhibited a progressive decline (HC: 1.31 ± 0.12 → MCI: 1.26 ± 0.09 → AD: 0.87 ± 0.19; p < 0.001 for AD vs. HC/MCI). Bilateral FA reductions plateaued in MCI (left: 0.57 ± 0.11 vs. HC: 0.82 ± 0.07, p < 0.001; right: 0.57 ± 0.11 vs. HC: 0.80 ± 0.07, p < 0.001) without further progression at the AD stage. MD showed a right-lateralized progression (HC → MCI → AD: left 0.53 → 0.74 → 0.78, right 0.51 → 0.71 → 0.77; p < 0.001), with a significant increase only in right MD from MCI to AD (p = 0.014). CSF biomarkers revealed a hierarchical depletion of Aβ42 (AD: 370.7 ± 145.9 vs. HC: 910.8 ± 191.5 pg./mL, p < 0.001) and accumulation of tau (t-tau: AD>MCI > HC, p < 0.001). Receiver operating characteristic (ROC) analysis identified right hippocampal MD and t-tau as optimal classifiers for AD.ConclusionThe framework reveals distinct biomarker trajectories: DTI-ALPS distinguishes symptomatic AD from preclinical stages, while right hippocampal MD progression reflects tau-mediated neurodegeneration. Early FA reductions in MCI combined with CSF profiles suggest a hierarchical staging model: amyloid-associated perivascular dysfunction is associated with asymmetric tau-driven hippocampal degeneration. This multimodal approach provides clinically actionable biomarkers for AD progression monitoring.